A novel fully human anti-ROR1 antibody PBA-0405 optimized for ADCC, induces potent anti-tumor activity against both solid and hematological malignancies - Veitonmäki, Niina; Kostyn, Anna; Kołt, Sonia; Ziemblicka, Aleksandra; Romanowska, Beata; Oleksy, Sabina; Krzywińska, Ewelina; Sołtys, Kamilla; Świderski, Łukasz; Naporowski, Piotr; Mamczur, Piotr; Świtoń, Monika; et al. (Frontiers in Immunology, 2025)
IntroductionB-cell malignancies, including chronic lymphocytic leukemia (CLL), pose a significant clinical challenge due to high relapse rates and dose-limiting toxicities seen with current therapies, particularly in elderly patients. Receptor tyrosine kinase-like orphan receptor 1 (ROR1) is an attractive therapeutic target due to its high expression on malignant B-cells and minimal presence in normal adult tissues, allowing the development of more potent and safer drugs for cancer treatment. PBA-0405 (called 2.0405.aF in this manuscript) is a novel, fully human afucosylated anti-ROR1 monoclonal antibody, specifically engineered for optimal induction of antibody-dependent cellular cytotoxicity (ADCC) to improve treatment of cancer.MethodsWe evaluated 22.0405.aF for ADCC activity and tumor-cell killing in comparison with clinically tested anti-ROR1 antibodies, including zilovertamab and R12. Functional assessment included in vitro cytotoxicity assays, ex vivo killing of patient-derived malignant B cells, and in vivo testing in humanized mice and murine xenograft models of hematologic and solid tumors. Safety was assessed through monitoring of healthy B-cell viability and toxicity in vivo.Results and discussionOur findings demonstrate that 22.0405.aF exhibits far superior ADCC activity compared to anti-ROR1 antibodies, e.g. zilovertamab and R12, tested in clinical trials thus far. 22.0405.aF displayed potent tumor cell killing, both in vitro and in vivo, and induced more potent killing of patient-derived malignant B-cells ex vivo compared to rituximab, without affecting healthy B-cells. Furthermore, in humanized mice, in murine xenograft models of both hematological and solid tumors, 22.0405.aF treatment induced robust inhibition of tumor growth without detectable toxicity.ConclusionThese results underscore the therapeutic potential of 22.0405.aF as a promising immunotherapy for treatment of ROR1-positive B-cell malignancies. Notably, 22.0405.aF has recently completed Phase 0 clinical trials in patients with head and neck carcinomas and soft tissue sarcomas, paving the way for further clinical development.